Effect of Morinda citrifolia (Noni)-Enriched Diet on Hepatic Heat Shock Protein and Lipid Metabolism-Related Genes in Heat Stressed Broiler Chickens - Flees, Joshua; Rajaei-Sharifabadi, Hossein; Greene, Elizabeth; Beer, Lesleigh; Hargis, Billy M.; Ellestad, Laura; Porter, Tom; Donoghue, Annie; Bottje, Walter G.; Dridi, Sami (Frontiers in Physiology, 2017)
Heat stress (HS) has been reported to alter fat deposition in broilers, however the underlying molecular mechanisms are not well defined. The objectives of the current study were, therefore: 1) to determine the effects of acute (2 hr) and chronic (3 wks) HS on the expression of key molecular signatures involved in hepatic lipogenic and lipolytic programs and 2) to assess if diet supplementation with dried Noni medicinal plant (0.2% of the diet) modulates these effects. Broilers (480 males, 1 d) were randomly assigned to 12 environmental chambers, subjected to two environmental conditions (HS, 35°C vs. TN, 24°C) and fed two diets (control vs. Noni) in a 2x2 factorial design. Feed intake and body weights were recorded, and blood and liver samples were collected at 2h and 3 wks post-heat exposure. HS depressed feed intake, reduced body weight, and up regulated the hepatic expression of heat shock protein HSP60, HSP70, HSP90 as well as key lipogenic proteins (fatty acid synthase, FASN; acetyl co-A carboxylase alpha, ACCα and ATP citrate lyase, ACLY). HS down regulated the hepatic expression of LPL and LIPC, but it up regulated that of ATGL. Although it did not affect growth performance, Noni supplementation regulated the hepatic expression of lipogenic proteins in a time- and gene-specific manner. Prior to HS, Noni increased ACLY and FASN in the acute and chronic experimental conditions, respectively. During acute HS, Noni increased ACCα, but reduced FASN and ACLY expression. Under chronic HS, Noni up regulated ACCα and FASN but it down regulated ACLY. In vitro studies, using chicken hepatocyte cell lines, showed that HS down regulated the expression of ACCα, FASN, and ACLY. Treatment with quercetin, one bioactive ingredient in Noni, up regulated the expression of ACCα, FASN, and ACLY under TN conditions, but it down regulated ACCα and increased ACLY levels under HS exposure. In conclusion, our findings indicate that HS induces hepatic lipogenesis in chickens and this effect is probably mediated via HSPs. The modulation of hepatic HSP expression suggest also that Noni might be involved in modulating the stress response in chicken liver.